Como o método de observação direta do comportamento do bebê e da criança pode contribuir para avanço da pesquisa clínica psicanalítica? - Saboia, Camila (2010)
This article introduces a frame of reflexion about the links between "the method of observation" and "method of treatment" in the field of research in clinical psycho-analysis. Early clinic leads to necessarily reconsider the object of the study, as it is about intervening at an early stage, before the language appears. To that extent, the question is raised whether the metaphoric value of the language could be compared to the value of the baby's gestures and behaviour. Winnicott, by highlighting the difference between "primitive" and "profound", offers new ways to understand that the "child in observation" and the "child in analytic cure" are no longer antagonist, but complementary.